Constructing a patient‐specific computer model of the upper airway in sleep apnea patients. (23rd August 2017) - Dhaliwal, Sandeep S.; Hesabgar, Seyyed M.; Haddad, Seyyed M. H.; Ladak, Hanif; Samani, Abbas; Rotenberg, Brian W.
Abstract : Objective: The use of computer simulation to develop a high‐fidelity model has been proposed as a novel and cost‐effective alternative to help guide therapeutic intervention in sleep apnea surgery. We describe a computer model based on patient‐specific anatomy of obstructive sleep apnea (OSA) subjects wherein the percentage and sites of upper airway collapse are compared to findings on drug‐induced sleep endoscopy (DISE). Study Design: Basic science computer model generation. Methods: Three‐dimensional finite element techniques were undertaken for model development in a pilot study of four OSA patients. Magnetic resonance imaging was used to capture patient anatomy and software employed to outline critical anatomical structures. A finite‐element mesh was applied to the volume enclosed by each structure. Linear and hyperelastic soft‐tissue properties for various subsites (tonsils, uvula, soft palate, and tongue base) were derived using an inverse finite‐element technique from surgical specimens. Each model underwent computer simulation to determine the degree of displacement on various structures within the upper airway, and these findings were compared to DISE exams performed on the four study patients. Results: Computer simulation predictions for percentage of airway collapse and site of maximal collapse show agreement with observed results seen on endoscopic visualization. Conclusion: Modeling the upper airway in OSA patients is feasible and holds promise in aiding patient‐specific surgical treatment. Level of Evidence: NA. Laryngoscope, 128:277–282, 2018